Aquifer Recharge Estimate and Framework of Water Bodies in Partially Forested Sub-Basins in the Northwest of Rio Grande do Sul - Graepin, Cristiane; Mancuso, Malva Andrea; Camargo, Mariza; Silva, José Luiz Silvério da; Borba, Willian Fernando de (Anuário do Instituto de Geociências, 2016)
Groundwater has become an important source for water supply, due the increase of restriction for surface water supply, today with scarcity and poor quality conditions. This study aims to estimate the groundwater recharge of SASG and the surface water quality from two small watershed. The watersheds, with different land use, are located at northwest of Rio Grande do Sul State. The groundwater recharge was calculated base on the drain flow rate data, collected in dry conditions. To estimate the runoff time in each watershed it was calculated the concentration time. The flow rate on a dry period was considered as water withdraw from the aquifer. The monitoring program included physical and chemical data from surface water measured during a hydrological year. The land use was mapped base on Google Earth images. The recharge was estimated in 0,58252 m3/year/m2 in the watershed 1 and 0,95476 m3/year/m2 in the watershed 2. The watershed 2 has higher forest land use. According to the water use classification, indicated in the legislation, the surface water is classified as from Class 1.